Comparison of antioxidant activity of compounds isolated from guava leaves and a stability study of the most active compound - Nantitanon W. (2014)
Tolerance to morphine analgesia following repeated administration disturbs the continuation of opioid therapy for severe pain. Emerging evidence suggests that the development of morphine tolerance may be antagonized by painful stimuli. To clarify the detailed mechanisms of these phenomena, we examined the effects of several pain stimuli on morphine-induced tolerance. Subcutaneous (s.c.) injection of morphine (10 mg/kg) produced an analgesic effect, which was evaluated by tail-pinch test. Morphine-induced analgesia was diminished by repeated administration of morphine (10 mg/kg, s.c.) once a day for 5 days, demonstrating the development of tolerance. Morphine analgesic tolerance was suppressed by nerve injury-induced neuropathic pain and formalin- or carrageenaninduced inflammatory pain. Tolerance to serum corticosterone elevation by morphine (10 mg/kg), which was evaluated by fluorometric assay, was also suppressed by formalin-induced inflammatory pain. Moreover, morphine analgesia induced by intracerebroventricular (10 nmol) or intrathecal (5 nmol) injection was diminished by repeated administration of morphine s.c., and this was also suppressed by carrageenan-induced inflammatory pain. These results suggest that morphine tolerance is inhibited by several pain stimuli, including neuropathic and inflammatory pain, through central mechanisms.